Stretchable, Injectable, and Self-Healing Conductive Hydrogel Enabled by Multiple Hydrogen Bonding toward Wearable Electronics - Chen, Jingsi; Peng, Qiongyao; Thundat, Thomas; Zeng, Hongbo (Chemistry of materials, 2019)
Conducting polymer hydrogels have been employed in diverse fields such as energy storage and bioelectronics, which possess both the mechanical properties of hydrogels and electronic transport properties of conducting polymers. However, the rigid and fragile nature of conducting polymers hinders the long-time stability of the hydrogels and limits their applications in emerging flexible electronic devices. In this work, we have developed a novel type of multifunctional conductive polymer hydrogel, of which high conductivity is integrated with excellent stretchability, injectability, and rapid self-healing capability, by incorporating multiple hydrogen-bonding 2-ureido-4[1H]-pyrimidinone (UPy) groups as cross-linking points into a brittle polyaniline/poly(4-styrenesulfonate) (PANI/PSS) network. The formation of the interpenetrating PANI/PSS network offers the hydrogel electronic conduction assisted by ionic transport, showing a conductivity of 13 S/m and a linear response (gauge factor = 3.4) to external strain (≈300%), with accurate and reliable detection of various human motions. Taking advantage of the reversibility of the noncovalent cross-links, the hydrogels can be facilely molded into different shapes and demonstrate a complete self-healing within 30 s upon damage. The combination of supramolecular chemistry with conducting polymers enables multifunctionalities in the conductive hydrogel, providing new insights into the design of advanced functional materials with applications in 3D printing, wearable devices, and flexible electronics.